On the Klein–Gordon oscillator in topologically charged Ellis–Bronnikov-type wormhole spacetime - Soares, A. R.; Vitória, R. L. L.; Aounallah, H. (European physical journal plus, 2021)
In this article, we have investigated a bosonic relativistic quantum oscillator in a topologically charged Ellis–Bronnikov-type wormhole spacetime. Through a purely analytical mathematical analysis, we determine the lowest energy state of relativistic energy of this quantum oscillator, which is influenced by the considered background. This influence is explicit due to the dependence of the allowed values of the lowest energy state of the system by the parameters that represent the wormhole throat and the global monopole charge. In addition, we show that it is not possible to determine a mathematical expression to represent the relativistic energy spectrum of the system.